IMPLEMENTASI KONSEP BISNIS DAN SHARIA ENTREPRENEURSHIP DALAM PENGEMBANGAN EKONOMI UMAT;PERSPEKTIF EKONOMI ISLAM - Nurul Fitrah Ilham; Supriadi; Mukhtar Lutfi; Nurafifah; A. Adi Putra (JSE: Jurnal Sharia Economica, 2026)
The rapid development of the global economy, accompanied by increasing business competition and digital transformation, requires an entrepreneurial model that not only emphasizes economic profit but also upholds ethical values, social responsibility, and sustainability. In this context, sharia entrepreneurship offers an alternative business approach by integrating Islamic principles into entrepreneurial activities to achieve both economic prosperity and social welfare. This study aims to analyze the implementation of Islamic business concepts and sharia entrepreneurship in promoting community economic development from the perspective of Islamic economics. The research employed a qualitative approach using the library research method. Data were collected from the Qur'an, Hadith, books, scientific articles, national and international journals, and other relevant literature, and were analyzed using content analysis. The findings indicate that sharia entrepreneurship is founded upon the principles of tawhid, justice, trustworthiness, honesty, professionalism, and public welfare. Its implementation contributes to employment creation, income generation, economic independence, and equitable wealth distribution through Islamic economic instruments. Furthermore, from the perspective of maqashid al-shariah, sharia entrepreneurship supports the protection of religion, life, intellect, lineage, and wealth. Therefore, strengthening the sharia entrepreneurship ecosystem is essential for fostering sustainable, inclusive, and equitable community economic development based on Islamic values.